CM-352 Efficacy in a Mouse Model of Anticoagulant-Associated Intracranial Hemorrhage - Navarro-Oviedo, Manuel; Marta-Enguita, Juan; Roncal, Carmen; Rodríguez, Jose A.; Zandio, Beatriz; Lecumberri, Ramón; Hermida, Jose; Oyarzabal, Julen; Pineda-Lucena, Antonio; Páramo, Jose A.; Muñoz, Roberto; Orbe, Josune (Thrombosis and Haemostasis, 2022)
Background Intracranial hemorrhage (ICH) is one of the major devastating complications of anticoagulation. Matrix metalloproteinase (MMP) inhibition has been proposed as a novel pharmacological approach for ICH treatment.Objectives We evaluated the effects of CM-352 (MMP-fibrinolysis inhibitor) in an experimental ICH model associated with oral anticoagulants as compared with clinically used prothrombin complex concentrate (PCC).Methods ICH was induced by collagenase injection into the striatum of wild type (C57BL/6J) anticoagulated mice (warfarin or rivaroxaban) and Mmp10 −/− mice. Hematoma volume and neurological deficits were measured 24 hours later by diaminobenzidine staining and different behavioral tests. Circulating plasminogen activator inhibitor-1 (PAI-1) activity and interleukin-6 (IL-6) were measured in plasma samples and local inflammation was assessed by neutrophil infiltration. Finally, fibrinolytic effects of MMP-10 and rivaroxaban were evaluated by thromboelastometry and thrombin-activatable fibrinolysis inhibitor (TAFI) activation assays.Results Only PCC reduced hemorrhage volume and improved functional outcome in warfarin-ICH, but both PCC and CM-352 treatments diminished hemorrhage volume (46%, p < 0.01 and 64%, p < 0.001, respectively) and ameliorated functional outcome in rivaroxaban-ICH. We further demonstrated that CM-352, but not PCC, decreased neutrophil infiltration in the hemorrhage area at 24 hours. The effect of CM-352 could be related to MMP-10 inhibition since Mmp10 −/− mice showed lower hemorrhage volume, better neurological score, reduced IL-6 levels and neutrophil infiltration, and increased PAI-1 after experimental ICH. Finally, we found that CM-352 reduced MMP-10 and rivaroxaban-related fibrinolytic effects in thromboelastometry and TAFI activation.Conclusion CM-352 treatment, by diminishing MMPs and rivaroxaban-associated fibrinolytic effects, might be a novel antihemorrhagic strategy for rivaroxaban-associated ICH.
Keywords: anticoagulants; fibrinolysis; hemorrhagic; stroke; matrix metalloproteinases; thrombosis